Effect of the inclusion of pisonay meal (Erythrina edulis) of three regrowth ages on the productive characteristics in guinea pigs (Cavia porcellus) - Cárdenas-Villanueva, Ludwing A. (2021)
The aim of this study was to evaluate the effect of three regrowth ages and three levels of inclusion of pisonay (Erythrina edulis) meal on feed consumption and conversion; body weight gain, and carcass rate in guinea pig fattening (Cavia porcellus). Shade-dried leaves and petioles of harvested trees were used and mechanically processed to 2 mm particle size. In total, 120 improved male guinea pigs were used, distributed in 10 treatments (3 regrowth ages, three levels of meal inclusion and a control group with alfalfa meal) for 56 days. The total and daily weight gain, in addition to the feed conversion had a similar response between treatments; feed consumption was lower with the 8M30% treatment (54.0 g/day) with respect to CA20% (59.3 g/day) (p<0.05) and the carcass yield was higher in 4M20% (73.5%) compared to the control diet (71.1%) (p<0.05). Feed consumption (60.3 g/day) as feed conversion (5.3) was higher at 12 months of regrowth age (p<0.05) with respect to 4 and 8 months, which were similar to each other. Carcass yield was similar (72%) with the inclusion of 10 and 20% and decreased (70.6%) with 30% pisonay meal (p<0.05). The pisonay meal used as a feed input for the production of concentrate does not affect the productive characteristics of guinea pigs.